An observational study on variation in the relations and branches of recurrent laryngeal nerve - K., Sailaja (International Journal of Research in Medical Sciences, 2017)
Background: Recurrent laryngeal nerve is one of the most important nerves because; it is subjected too much variation in its site, branches and relation with the branches of inferior thyroid artery and to thyroid gland. Therefore, the present study was undertaken to study the variation in the relations and branches of recurrent laryngeal nerve. Methods: The present study was undertaken in postmortem specimen from Forensic department and cadavers in the dissection hall after the ethical clearance. The specimens were collected enbloc including tongue, oesophagus and trachea. Also, the specimens were used for modified Sihler’s technique. Specimen was dissected and recurrent laryngeal nerve was identified. Its relation and branches were noted. The data regarding the number of branches, level of branching, anastomoses were expressed as percentages. Results: Recurrent laryngeal nerve does not always lie in the trachea-oesophageal sulcus. It lies lateral to trachea. This relation is found more on the right side than on the left side. The relation of the nerve to inferior thyroid artery was considered. It was found that, the nerve was lying posterior to the artery more commonly. There is no significant difference between right and left sides. The division of the nerve into anterior and posterior branches before entering the larynx was observed in half of the specimens, nerve divided before entry into the larynx. In most cases, the level of division was 1 cm below the cricothyroid joint. In few specimens, it varied from 2 to 4 cm. Conclusions: The variation in the position is more common on the right side. Branches may arise from the nerve about 4cm below the cricothyroid joint. It lies posterior to the inferior thyroid artery more frequently.